Examining Middle School Students’ Cognitive Structures and Visual Images Regarding The Concept Of Laboratory - Özdemir Onaç, Elif (Research Trends In Educational Sciences, 2025)
This study aims to examine middle school students' cognitive structures and visual images regarding the concept of "laboratory." The study group consists of 296 students enrolled in a public middle school in Ankara during the 2024-2025 academic year. The research employs a survey model, one of the quantitative research approaches. Data were collected through a word association test and student drawings related to the concept of the laboratory. The data obtained from the study were analyzed using content analysis with the MAXQDA-11 software package. The findings indicate that students primarily associate the laboratory concept with laboratory equipment, followed by its functions. Middle school students most frequently associated the term "laboratory" with the word "experiment" (n=140) and least frequently with the word "magnifier" (n=8). An analysis of the student drawings revealed that the laboratory was predominantly depicted with chemical experiment tools such as test tubes, spirit burners, and beakers. Fifth-grade students were more likely to associate the concept of the laboratory with laboratory rules and hazards. This result could be attributed to fifth-grade students receiving four lesson hours of laboratory safety instruction as part of the 2024 Science Curriculum. Notably, as the grade level increases, students demonstrate a broader range of word associations related to the laboratory. However, the increase in grade level does not affect students' visual representations of the laboratory.